CONFORTO TÉRMICO EM ESPAÇOS ABERTOS: O ESTADO DA ARTE DO UNIVERSAL THERMAL CLIMATE INDEX - UTCI NO BRASIL - Silva, Thiago José Vieira; Hirashima, Simone Queiroz da Silveira (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Urban climate studies have been increasingly considered for urban planning decisions, mainly in large metropolises. For this purpose, the evaluation of the thermophysiological effects of the microclimatic conditions on the human beings is one of the key issues. There are several important aspects to be taken into account for the definition of thermal comfort conditions outdoors. Microclimatic and individual parameters, among others, are relevant, and thermal indices are used for representing their integrated effect. Currently, the Universal Thermal Climate Index (UTCI) has been regarded as one of the most suitable tools for this goal. In this context, the authors aimed to identify the state of the art of UTCI studies in Brazil, since it was internationally launched in 2001. The method adopted encompassed a Proknow-C's Bibliometric Investigation and an Analysis Process. The results show that, up to now, there are few studies on this subject in the Brazilian context, and that very few researchers have worked with this thematic. The studies themes were categorized and presented. The authors concluded that, although incipient in Brazil, studies on the UTCI index have wide application as subsidies for urban design and, consequently, large potential for contributing to better climatic conditions in cities.